2010
DOI: 10.1902/jop.2010.100044
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Destructive Periodontal Disease: A Systematic Review

Abstract: Men appear at greater risk for destructive periodontal disease than women; however, men do not appear at higher risk for more rapid periodontal destruction than women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
121
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(156 citation statements)
references
References 71 publications
26
121
3
6
Order By: Relevance
“…From data of systematic review and oral-systemic research expands to include genetics and immunity in general, authors found the same distribution like our research where males' sex was prevalent: Shiau HJ et al (2010) a systematic review of the literature and meta-analyses in sex differences in destructive periodontal disease estimates sex-related differences in the prevalence of periodontitis in men 37.4% versus 28.1%, respectively [9]. Dan Sindelar, DMD (2015) found that men are at greater risk for developing destructive periodontal disease than women due to heightened innate immune response in men compared to women [10].…”
Section: Discussionsupporting
confidence: 83%
“…From data of systematic review and oral-systemic research expands to include genetics and immunity in general, authors found the same distribution like our research where males' sex was prevalent: Shiau HJ et al (2010) a systematic review of the literature and meta-analyses in sex differences in destructive periodontal disease estimates sex-related differences in the prevalence of periodontitis in men 37.4% versus 28.1%, respectively [9]. Dan Sindelar, DMD (2015) found that men are at greater risk for developing destructive periodontal disease than women due to heightened innate immune response in men compared to women [10].…”
Section: Discussionsupporting
confidence: 83%
“…This study also shows that there is a high prevalence of periodontal diseases in the local government area and is commoner in the age group 16-25 years(27.2%). The prevalence of periodontal disease increases with age (Maduakor et (Shiau and Reynolds, 2010). This study also demonstrated that the prevalence of periodontal disease among the respondents was more in the middle and lower socio-economic group.…”
Section: Discussionsupporting
confidence: 58%
“…Zupnik et al 18 reported that gender was the parameter with the strongest correlation with implant failure in a metaanalysis that demonstrated that males had a higher prevalence of destructive periodontal disease. 19 Because periodontal disease is widely recognized as a risk factor for peri-implantitis and implant failure, 20,21 the higher prevalence of periodontal disease in males may explain the outcome of the study. Anitua et al 22 reported significantly lower survival for implants placed in the maxilla compared to the mandible.…”
Section: Discussionmentioning
confidence: 98%